Kinematic analysis of back somersault pike according to skill level in platform diving - Park, J.; Yoon, S. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this study was to investigate kinematic differences in back pike somersault in platform diving according to skill level and to apply the findings to improve performance. Method: Korean divers participating in this study were divided into a skilled group (age: 21.6±4.16 y, height: 1.68±0.03 m, weight: 62.0±3.94 kg, career: 12.6±5.13 y) and a less-skilled group (age: 20.6±2.7 y, height: 1.72±0.05 m, weight: 64.8±6.76 kg, career: 12.2±2.49 y) and an independent t-test was performed to analyze differences between groups at the moment of takeoff. Results: The two groups showed significant differences in displacement and velocity of center of mass (COM), takeoff angle, hip joint angle, knee joint angular velocity, and hip joint angular velocity at the takeoff (p<.05), and significant differences in displacement of COM, hip joint, and ankle joint during flight (p<.05). Conclusion: For a successful back pike, the COM should rise quickly in the vertical direction and the hip joint angle and angular velocity should increase. To improve performance, the back pike turn should be practiced on the ground before an attempt on a 10-m platform, to stretch the ankle and knee joints and enable quick flexion of the hip joint when turning in flight.